Productivity and the Investment Climate: What Matters Most? - Bastos, Fabiano; Nasir, John (World Bank, Washington, D.C., 2013)
The authors explore the links between the investment climate and firm-level productivity and attempt to identify which dimensions of the investment climate matter most for productivity. Their analysis is based on data collected in a recent investment climate survey of garment and food processing firms in five countries in Eastern Europe and Central Asia. The authors use the first principal components of a series of indicators to summarize broad aspects of the investment climate and identify those most important in determining productivity. Their results indicate that competitive pressure is the most critical factor in the investment climate, accounting for more variation in firm-level productivity than infrastructure provision or issues related to government rent seeking and bureaucratic burden. This suggests that to improve productivity, increase output, and reduce poverty, policymakers should focus reform efforts on removing barriers to entry and creating open, highly competitive markets.